Expressive Vocabulary Growth After Pediatric Auditory Brainstem Implantation in Two Cases' Spontaneous Productions: A Comparison With Children With Cochlear Implants and Typical Hearing - Faes, Jolien; Gillis, Steven (Frontiers in Pediatrics, 2019)
Auditory brainstem implants (ABI) are recently being used to restore hearing of children with a congenital hearing loss, due to for instance the absence of auditory nerves. Thus far, the literature has focused on perceptual outcomes. The present study is among the first ones to investigate the spoken language development after implantation. The lexical development of children with ABI is examined longitudinally in comparison to children with typical hearing and children with cochlear implants. Results show that children with ABI still have smaller spoken vocabularies as compared to (hearing) age-matched children with cochlear implants and children with typical hearing. Implications will be discussed.